AI sebagai Alat Transformasi Organisasi: Peran AI dalam Meningkatkan Produktivitas dan Efektivitas Pemimpin - Ahmad Rifqi Dwi Putra; Halimatus Zahro; Hikmatul Maula; Mochammad Isa Anshori (CV. Aksara Global Akademia, 2025)
Artificial intelligence (AI) has become a critical tool for transforming organizations in the ever-evolving digital age. In this article, we will discover the various ways in which AI can improve the efficiency and productivity of leaders in various industries. Leaders can focus on strategy and innovation by optimizing work processes and making faster and more accurate decisions with the help of in-depth data analysis. This article shows how AI can help organizational performance and how leaders can use it to achieve long-term goals. The results are expected to provide guidance to leaders and decision-makers on how to use AI to drive change in their companies.